2011
DOI: 10.1200/jco.2010.32.4962
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Trial of Lenalidomide and CCI-779 in Patients With Relapsed Multiple Myeloma: Evidence for Lenalidomide–CCI-779 Interaction via P-Glycoprotein

Abstract: The MTD of this combination regimen was 25 mg lenalidomide with 15 mg CCI-779, with toxicities of fatigue, neutropenia, and electrolyte wasting. Pharmacokinetic and clinical interactions between lenalidomide and CCI-779 seemed to occur, with in vitro data indicating lenalidomide was an ABCB1 (P-gp) substrate. To our knowledge, this is the first report of a clinically significant P-gp-based drug-drug interaction with lenalidomide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 39 publications
1
57
0
Order By: Relevance
“…While passive diffusion likely plays a role in its absorption, the high bioavailability and absorption of protonated lenalidomide may also be facilitated by transporter-mediated pathways. Approximately 90% of lenalidomide clearance occurs primarily by renal excretion, and a portion of this is believed to be transporter mediated (21,23). Renal reabsorption has not been directly studied for lenalidomide, and it is therefore unknown if this contributes to its overall disposition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While passive diffusion likely plays a role in its absorption, the high bioavailability and absorption of protonated lenalidomide may also be facilitated by transporter-mediated pathways. Approximately 90% of lenalidomide clearance occurs primarily by renal excretion, and a portion of this is believed to be transporter mediated (21,23). Renal reabsorption has not been directly studied for lenalidomide, and it is therefore unknown if this contributes to its overall disposition.…”
Section: Introductionmentioning
confidence: 99%
“…The authors evaluated a Michaelis-Menten function to describe this perceived nonlinearity, but ultimately utilized a dose-proportional model which fit the data equally well. In addition to humans (21,23,24,28), pharmacokinetic studies of lenalidomide have been reported in rats and monkeys (3,29).…”
Section: Introductionmentioning
confidence: 99%
“…The in vitro studies proved that lenalidomide is actively transported by P-gp and this effect was reversed by CCI-779 and verapamil. In addition, ABCB1 silencing RNA or short interfering RNA (siRNA) knockdown studies in vitro also showed more lenalidomide uptake, supporting lenalidomide and P-gp drug-drug interaction (154).…”
Section: Discussionmentioning
confidence: 99%
“…In light of emerging studies that these novel drugs that have been incorporated to MM therapeutic management are substrates of ABC transporters, the situation warrants a re-evaluation of the manipulative power of MM cells (154). It is evident that opting for more aggressive chemotherapy has brought some promise of prolonging remission and survival in MM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation